2015
DOI: 10.1371/journal.pone.0138438
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and Progesterone Receptors Are Targets for Bisphenol A (BPA), 4-Methyl-2,4-bis-(P-Hydroxyphenyl)Pent-1-Ene—A Potent Metabolite of BPA, and 4-Tert-Octylphenol: A Computational Insight

Abstract: Exposure to toxic industrial chemicals that have capacity to disrupt the endocrine system, also known as endocrine disrupting chemicals (EDCs), has been increasingly associated with reproductive problems in human population. Bisphenol A (BPA; 4,4'-(propane-2,2-diyl)diphenol) and 4-tert-octylphenol (OP; 4-(1,1,3,3-tetramethylbutyl)phenol) are among the most common environmental contaminants possessing endocrine disruption properties and are present in plastics, epoxy resins, detergents and other commercial prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…BPA has the ability to bind and activate estrogen receptor (ER) subtypes (i.e., ERα, ERβ and particularly ERγ) (Teng et al, ). It has also been suggested to disturb the normal functioning of ER receptors, although it has lower affinity for nuclear ERs than estradiol (Rehan et al, ). Due to abundant exposure, the general population has higher circulating concentrations of BPA when compared to estradiol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPA has the ability to bind and activate estrogen receptor (ER) subtypes (i.e., ERα, ERβ and particularly ERγ) (Teng et al, ). It has also been suggested to disturb the normal functioning of ER receptors, although it has lower affinity for nuclear ERs than estradiol (Rehan et al, ). Due to abundant exposure, the general population has higher circulating concentrations of BPA when compared to estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…Due to abundant exposure, the general population has higher circulating concentrations of BPA when compared to estradiol. BPA can also disrupt androgenic signaling pathways, which play important roles in male sex organ development and reproductive functions (Rehan et al, ; Sidorkiewicz, Zaręba, Wołczyński, & Czerniecki, ; Teng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, BPA has been shown to bind the estrogen receptors (ERα and ERβ) (Delfosse et al, 2012), GPR30 (or GPER) (Pupo et al, 2012) and ERRγ with a high affinity (Liu et al, 2012). It also directly or indirectly interferes with the activity of the androgen receptor (AR), the progesterone receptor (PGR), the glucocorticoid receptor (GR), and the PPARγ (Acconcia et al, 2015; Rehan et al, 2015). The mechanism of action of BPA in dental cells is even less evident as its putative receptors are poorly defined in dental tissues, except for ERα (Jedeon et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between BPA, diabetes and obesity [82,130,131], hormone dependent cancers and reproductive impairment is well documented in animals but still limited to case studies [132] and to controversial data in human. Several metabolites of BPA are also being investigated as suspected endocrine disruptors [133]. The molecule was originally considered to show weak affinity for the estrogen receptors, however recent studies have shown it to be rather more effective than previously thought.…”
Section: Bisphenol Amentioning
confidence: 99%